2016
DOI: 10.1097/md.0000000000002924
|View full text |Cite
|
Sign up to set email alerts
|

Biological and Prognostic Significance of the Morphological Types and Vascular Patterns in Colorectal Liver Metastases (CRLM)

Abstract: Patients with encapsulated colorectal liver metastases (CRLM) have a better prognosis than those without a capsule. The reason for the encapsulation is unknown. Hypoxia inducible factor-1α (HIF-1α) increases tumor angiogenesis and tumor tissue expression is associated with reduced survival. Our aim was to determine whether the good prognosis of encapsulated CRLM is associated with reduced HIF-1α expression by the cancer.The study selected only patients who had not undergone neoadjuvant chemotherapy prior to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…We found that in addition to the four studies in which the desmoplastic pattern was a separate parameter, a ‘mixed’ pattern was reported independently of the three main patterns in a further three studies, 14 15 44 and independently of the desmoplastic and replacement patterns in a fourth. 28 Frequencies for a mixed pattern were 18.6% 15 and 17.6% 14 in two larger cohorts and 10% 28 and 41.4% 44 in two smaller ones. Intralesional heterogeneity was also reflected indirectly in some studies that did not quantify this feature, stating that heterogeneity was ‘uncommon’, 31 or that ‘usually’ or ‘in most of the cases’, only one growth pattern was present.…”
Section: Resultsmentioning
confidence: 85%
“…We found that in addition to the four studies in which the desmoplastic pattern was a separate parameter, a ‘mixed’ pattern was reported independently of the three main patterns in a further three studies, 14 15 44 and independently of the desmoplastic and replacement patterns in a fourth. 28 Frequencies for a mixed pattern were 18.6% 15 and 17.6% 14 in two larger cohorts and 10% 28 and 41.4% 44 in two smaller ones. Intralesional heterogeneity was also reflected indirectly in some studies that did not quantify this feature, stating that heterogeneity was ‘uncommon’, 31 or that ‘usually’ or ‘in most of the cases’, only one growth pattern was present.…”
Section: Resultsmentioning
confidence: 85%
“…reported that patients with a thick fibrous pseudocapsule (number of collagen bundles ≥10) had better 5‐year survival than patients with a thin fibrous pseudocapsule (number of collagen bundles <10) or no fibrous pseudocapsule (88% versus 64% and 31%, respectively, P < 0.001). Other studies have reported comparable results, noting that the absence of a tumour pseudocapsule was associated with worse survival and higher recurrence . Only one study has failed to demonstrate the prognostic significance of a tumour pseudocapsule .…”
Section: Presence Of a Tumour Pseudocapsulementioning
confidence: 90%
“…Other studies have reported comparable results, noting that the absence of a tumour pseudocapsule was associated with worse survival and higher recurrence. 63,75,[81][82][83][84][85] Only one study has failed to demonstrate the prognostic significance of a tumour pseudocapsule. 38 Recently, Fernand ez-Aceñero et al 70 reported an association between regression grade and the presence of a pseudocapsule after neoadjuvant chemotherapy (P = 0.009).…”
Section: Presence Of a Tumour Pseudocapsulementioning
confidence: 99%
“…TGFI inhibits the transforming growth factor β (TGF-β) signaling pathway, which plays a crucial role in fibrotic events as reported previously [ 28 ]. In line with the poor prognosis and lower overall survival rates reported for non-encapsulated CRLM [ 29 ], the upregulation of TGFI may be a hint towards a higher malignancy of the third and also last CRLM of the patient before he succumbed to the disease. Furthermore, in M3 in contrast to M1 and M2, we also observed a downregulation of laminin subunit beta-2 (LAMB2), decorin (DCN) and coagulation factor XIII A chain (F13A1), which are said to be associated with good prognosis in CRC (Fig.…”
Section: Resultsmentioning
confidence: 79%